Enhancing breadth of knowledge within multidisciplinary doctoral research: reflections from the Cambridge Generic Nutrition Training course for non-nutritionist postgraduates and professionals. (November 2016) - Laur, C.; Ball, L.; Crowley, J.; Bell, H.; Maddock, J.; Ray, S.
Highlights: Doctoral students need to have breadth and depth within the understanding of their field. Researchers require education on how to translate findings into meaningful improvements in public health. The Generic Nutrition Training supports doctoral students and researchers to increase their breadth of nutrition knowledge. Favourable evaluation of this course has resulted in a model that other research leaders can use.